Tumor‐suppressive miR‐323a inhibits pancreatic cancer cell proliferation and glycolysis through targeting HK‐2. Issue 12 (23rd November 2022) - Wei, Yangnian; Wang, Mingdong; Liang, Mingkun; Liu, Ling; Mo, Shifa; Zhang, Hongchang; Chen, Yunhui; Li, Nianfeng
Abstract: Pancreatic ductal adenocarcinoma (PDAC) accounts for more than 85% of all malignant pancreatic exocrine tumors and is one of the main causes of cancer‐related fatalities. PDAC is characterized by a high glycolytic rate to ensure its survival as a result of hypovascularization and the desmoplastic reaction. In this study, microRNA 323a (miR‐323a) was shown to be downregulated within pancreatic cancer tissues and cells, and enriched in the glucose metabolism pathway. In vitro, overexpression of miR‐323a suppressed cell viability, DNA synthesis, and colony formation; in vivo, miR‐323a overexpression suppressed the tumor growth within a xenograft mouse model. Regarding cellular glycolysis, miR‐323a overexpression decreased glucose‐6‐phosphate levels, inhibited glucose uptake, and reduced lactate and adenosine triphosphate production. miR‐323a was found to directly target hexokinase 2 (HK‐2) and negatively regulated HK‐2 expression. HK‐2 overexpression exerted oncogenic effects on pancreatic cancer cells and promoted cellular glycolysis; more importantly, HK‐2 overexpression partially eliminated the effects of miR‐323a overexpression. In conclusion, miR‐323a is downregulated within pancreatic cancer and serves as a tumor‐suppressive miRNA through inhibiting cancer cell proliferation and glycolysis. miR‐323a exerts its tumor‐suppressive effects through targeting HK‐2.